1988
DOI: 10.1111/j.1365-2044.1988.tb06626.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lignocaine levels during paediatric endoscopy of the upper respiratory tract

Abstract: SummaryPlcr.vnii lignocaine levels were measured at 5 . I0 Anaesthesia for routine endoscopy of the upper airway in children at Great Ormond Strcct Hospital involves the usc of a spontaneous ventilation technique with local application of lignocaine to inhibit the laryngeal reflexes. Previous studiesl-~" have shown that high plasma levels of local anxsthelics may be achieved from topical absorplion. The ralc of absorption Is thought to be related to the moistness of the mucosa of the upper airway and hence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…It is safe to use during upper airway endoscopy, with minimal potential for systemic toxicity. 69 In this review, we found that seven of 10 studies assessed the impact of topical lidocaine on upper airway obstruction and three reported an increase in airway obstruction; whereas four demonstrated no significant effect. The two studies assessing changes in sleep parameters showed conflicting results; one demonstrating an increase in mean apnea duration and the other no effect on frequency or duration of apneas or hypopneas.…”
Section: Effects Of Topical Lidocaine On the Airwaymentioning
confidence: 82%
See 1 more Smart Citation
“…It is safe to use during upper airway endoscopy, with minimal potential for systemic toxicity. 69 In this review, we found that seven of 10 studies assessed the impact of topical lidocaine on upper airway obstruction and three reported an increase in airway obstruction; whereas four demonstrated no significant effect. The two studies assessing changes in sleep parameters showed conflicting results; one demonstrating an increase in mean apnea duration and the other no effect on frequency or duration of apneas or hypopneas.…”
Section: Effects Of Topical Lidocaine On the Airwaymentioning
confidence: 82%
“…Lidocaine has a rapid onset of action (1–5 minutes) and intermediate duration of efficacy (10–15 minutes) when used topically. It is safe to use during upper airway endoscopy, with minimal potential for systemic toxicity . In this review, we found that seven of 10 studies assessed the impact of topical lidocaine on upper airway obstruction and three reported an increase in airway obstruction; whereas four demonstrated no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine 1% has two advantages for this application: (1) larger volumes can be used and (2) it has a short (10‐min) duration of action. Doses up to 4 mg·kg −1 have been used without complications but the dose may need to be reduced in patients younger than 2 years old and in those with dry mucosa (27).…”
Section: Induction Of Anaesthesia For Bronchoscopymentioning
confidence: 99%
“…This corresponds well with the observed clinical effect after an hour. Pharmacokinetic studies of lidocaine after topical administration to mucosal surfaces in children in doses of 3-4 mg kg ª1 have shown plasma concentrations above 2 mg ml ª1 after 5 to 10 min, indicating rapid absorption after mucosal application (4,12,13).…”
Section: Discussionmentioning
confidence: 99%